The Roles of CPG Phase Modulation and Reflexive Muscular Patterns in Balance Recovery During Walking—A Simulation Study - Yu Ikemoto; Wenwei Yu (Applied Bionics and Biomechanics)
Most walking assist systems reported are not available for real world environments where frequent perturbations are caused by slips, uneven terrain, slopes and obstacles. It is evident that humans are able to cope with such perturbations with reflexes that cause unconscious, relatively fixed muscular response patterns to perturbations within a short period of time. In our previous study, we showed that artificial reflexes could improve the perturbation resistance for simulated walkers, though the roles of different reflexive mechanisms were not quantitatively clarified. In this study, we focused on the different roles of reflexive muscle responses and the CPG phase modulation mechanism. By proposing and evaluating two stability criteria through a series of simulation experiments, we revealed different roles for two mechanisms in the simulated walkers. These will not only further increase the possibility of realising artificial reflexes for paralysed individuals, but also bring new insights into the field of motor control.